Pathways to care of patients with mental health problems in Bangladesh - Nuri, Nazmun Nahar; Beiersmann, Claudia; Jahn, Albrecht (International journal of mental health systems, 2018)
Health systems in Bangladesh are not fully organized to provide optimal care services to patients with mental health problems. There is both a lack of resources and a disproportional distribution of the available resources. To design an equitable health system and plan interventions to improve access to care, a better understanding of mental health care-seeking behavior and care pathways are crucial.